2020
DOI: 10.1259/bjr.20201042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastases using pre-treatment PET radiomics of the primary tumour in esophageal adenocarcinoma: an external validation study

Abstract: Objectives: To improve clinical lymph node staging (cN-stage) in esophageal adenocarcinoma by developing and externally validating three prediction models; one with clinical variables only, one with positron emission tomography (PET) radiomics only, and a combined clinical and radiomics model. Methods: Consecutive patients with fluorodeoxyglucose (FDG) avid tumours treated with neo-adjuvant therapy between 2010 and 2016 in two international centres (n = 130 and n = 60, respectively) were included. Four clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Our study established a radiomics-based clinical nomogram with a relatively larger sample size and validated on an external dataset. This was similar to previous findings that nomogram incorporating clinical factors and imaging features were of predictive value for EC patients [ 45 , 46 , 47 ]. Zhang et al [ 45 ] reported that a nomogram based on clinical variables and imaging radiomic features was predictive of lymph node metastases.…”
Section: Discussionsupporting
confidence: 92%
“…Our study established a radiomics-based clinical nomogram with a relatively larger sample size and validated on an external dataset. This was similar to previous findings that nomogram incorporating clinical factors and imaging features were of predictive value for EC patients [ 45 , 46 , 47 ]. Zhang et al [ 45 ] reported that a nomogram based on clinical variables and imaging radiomic features was predictive of lymph node metastases.…”
Section: Discussionsupporting
confidence: 92%
“…Applying the selection criteria led to 52 studies for full-text screening. At the end, a total of 37 articles were deemed eligible [ 28 64 ], including 30 articles within 5 years [ 28 38 , 41 43 , 45 , 47 50 , 52 54 , 57 64 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… HF PyRadiomics (V2.0.1) Clinical and classical PET Xie: 2020 [ 58 ] ESCC 2008–2014 CT 120 kV, 180–280 mA, 3 mm CCRT 57 HF IBEX (V1.0β) Clinical factors Hu: 2020 [ 29 ] ESCC 2007–2018 CT 120 kV, 200–400 mA 2.5 mm (inst 1) 5 mm (inst 2) voxel sizes: 1 × 1 × 5 mm3 nCRT 161 (train) 70 (test) HF PyRadiomics (V3.0) No Luo: 2020 [ 41 ] ESCC 2013–2015 CT 120 kV, 120 mAs, 5 mm dCCRT 160 (train) 66 (val.) HF 3DSlicer (V4.10.2) Clinical factors Li: 2020 [ 54 ] ESCC 2012–2019 CT 120 kV/140 kV, 140–300 mA, 5 mm nCRT 121 HF IBEX Clinical factors Zhang: 2020 [ 47 ] EAD 2010–2016 PET/ CT 120 kVp, 20–200 mA surgery alone, neoadjuvant chemotherapy, and nCRT 190 HF Matlab Clinical factors Du: 2020 [ 42 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the WB-PET-based radiomics model showed promising results in predicting occult lymph node metastasis in cN0 tumors, including lung cancer, cervical cancer, and esophageal adenocarcinoma [ 25 , 26 , 27 ]. Hasan et al analyzed the textural features of WB-PET/CT coming from 124 breast cancer patients and showed the gray-level zone length matrix (GLZLM) could be the predictive parameter of ALN, but the AUC was only 0.64 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%